(untitled) (Pulse, 2014)
Pregnancy is a rare event in patients with cirrhosis. Recent improvements in the treatment of chronic liver disease have resulted in higher conception rates and more successful pregnancy outcomes. Still pregnancy in cirrhosis is associated with high incidence of fetal loss as well as higher maternal mortality both during pregnancy and in the post-partum period. In this paper we described a case of a successful pregnancy in a young woman with advanced cirrhosis facing life threatening condition in her last trimester and perioperative period. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20191 Pulse Vol.5 January 2011 p.50-53